Detectability of Solar Rotation Period across Various Wavelengths - Valeriy Vasilyev; Timo Reinhold; Alexander I. Shapiro; Theodosios Chatzistergos; Natalie Krivova; Sami K. Solanki (The Astrophysical Journal Letters)
The light curves of old G dwarfs obtained in the visible and near-infrared wavelength ranges are highly irregular. This significantly complicates the detectability of the rotation periods of stars similar to the Sun in large photometric surveys, such as Kepler and TESS. In this study, we show that light curves collected in the ultraviolet (UV) wavelength range are much more suitable for measuring rotation periods. Motivated by the observation that the Sun’s rotational period is clearly discernible in the UV part of the spectrum, we study the wavelength dependence of the rotational period detectability. We employ the Spectral and Total Irradiance Reconstructions model to characterize the detectability of the solar rotation period across various wavelengths using the autocorrelation technique. We find that at wavelengths above 400 nm, the probability of detecting the rotation period of the Sun observed at a random phase of its activity cycle is approximately 20%. The probability increases to 80% at wavelengths shorter than 400 nm. These findings underscore the importance of UV stellar photometry.